Organization and Financing of Innovative Strategies for Rural Development - Irina Olimpia Susanu; Alina-Florentina Săracu; Sabin Maricel Murariu (Risk in Contemporary Economy)
In the given article, based on the analyzes of international and national strategies for enlarging innovative activity in agricultural production, there have been identified the main directions of using scientific and research potential, in the context of entering new technologies in the agro-industrial production sector. Relevant mechanisms for the purpose of state support for innovation activity were identified for Romania.